2011
DOI: 10.1590/s0004-282x2011000100016
|View full text |Cite
|
Sign up to set email alerts
|

Continuous ventricular cerebrospinal fluid drainage with intracranial pressure monitoring for management of posttraumatic diffuse brain swelling

Abstract: Background: Ventricular drainage has played an important role in the management of traumatic brain-injured patients. The aim of the present study was describe outcomes in a series of 57 patients with diffuse brain swelling underwent to intracranial pressure (ICP) monitoring. Method: Fifty-eight patients with diffuse posttraumatic brain swelling, were evaluated prospectively. The Glasgow Coma Scale (GCS) scores of patients varied from 4 to 12. Patients groups divided according to GCS and age. Patient neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 30 publications
1
20
0
11
Order By: Relevance
“…Similar to our experience, another study of 58 patients with continuous intracranial pressure monitoring by ventricular catheterization reported an overall infection rate of 8.6% [17]. Another study that was performed in our institution by Camacho et al on 119 patients who underwent EVD procedures showed an incidence of infection of 18.3%, and mortality was not significantly different between patients who were infected with Gram-negative (56%) or Gram-positive (50%) microorganisms.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to our experience, another study of 58 patients with continuous intracranial pressure monitoring by ventricular catheterization reported an overall infection rate of 8.6% [17]. Another study that was performed in our institution by Camacho et al on 119 patients who underwent EVD procedures showed an incidence of infection of 18.3%, and mortality was not significantly different between patients who were infected with Gram-negative (56%) or Gram-positive (50%) microorganisms.…”
Section: Discussionsupporting
confidence: 82%
“…A modest benefit of 10.1% ICP reduction was noted in patients with a mean baseline ICP of 26.2 mm Hg and 3 mL of CSF drainage. 25 In a 2011 study 26 of continuous CSF drainage, researchers found no difference in ICP reduction for patients with traumatic brain injury. More recently, in a study 23 of CSF drainage in patients with subarachnoid hemorrhage, researchers reported no difference in mean ICP values for patients with continuous versus intermittent CSF drainage.…”
Section: Tablementioning
confidence: 99%
“…On the one hand, this method can directly release cerebrospinal fluid and reduce intracranial pressure, drain out the harmful substances such as inflammatory chemokines, leukotriene C4, and interleukin-6, and reduce secondary damage. 11 On the other hand, it allows clinicians to monitor real-time changes in intracranial pressure, prevent damage caused by sharp fluctuations in intracranial pressure. Releasing a small amount of cerebrospinal fluid can significantly lower the intracranial pressure of PADBS patients.…”
Section: Discussionmentioning
confidence: 99%